2013
DOI: 10.1098/rsbl.2013.0270
|View full text |Cite
|
Sign up to set email alerts
|

Are men better than women at acoustic size judgements?

Abstract: Formants are important phonetic elements of human speech that are also used by humans and non-human mammals to assess the body size of potential mates and rivals. As a consequence, it has been suggested that formant perception, which is crucial for speech perception, may have evolved through sexual selection. Somewhat surprisingly, though, no previous studies have examined whether sexes differ in their ability to use formants for size evaluation. Here, we investigated whether men and women differ in their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 19 publications
6
31
2
Order By: Relevance
“…Our results show that this ability does not deteriorate with age. Previous studies report equivocal findings as to whether male listeners process size information differently from female listeners [3,9,10]. In our study, listener sex had no effect.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our results show that this ability does not deteriorate with age. Previous studies report equivocal findings as to whether male listeners process size information differently from female listeners [3,9,10]. In our study, listener sex had no effect.…”
Section: Discussioncontrasting
confidence: 84%
“…Several studies have demonstrated that sighted human listeners can accurately assess men's relative body size from the voice alone, typically associating lower fundamental and formant frequencies with larger size [3,9,10]. However, how we acquire this ability remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Following previous studies that had examined body size estimation using manipulated voice stimuli (e.g., Charlton, Taylor, & Reby, 2013;Pisanski, Oleszkiewicz, & Sorokowska, 2016;Rendall et al, 2007), participants rated the apparent Blargeness^of the person whose voice they heard on each trial, and they were not instructed as to which aspect of body size (height, weight) they should focus on during this task. This method allowed for our results to be more directly comparable to those of previous work examining body size estimation, but also to studies examining pitch-size associations more broadly (see, e.g., Ohala, 1984, andParise, 2016, for reviews).…”
Section: Methodsmentioning
confidence: 99%
“…When using manipulated vocal stimuli, most studies, including the present study, have asked participants to assess the body size of speakers on Blargeness,^without biasing listeners to focus on either height or weight (e.g., Charlton et al, 2013;Rendall et al, 2007). This is of course also the case for studies examining pitch-size mapping more broadly-for instance, between tones and inanimate objects (Parise, 2016, for a review), for which a height/weight distinction is less sensible.…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
See 1 more Smart Citation